Identifikasi Reptil Sub Ordo Serpentes Pada Ekosistem Gambut Hutan Desa Pematang Rahim Kabupaten Tanjung Jabung Timur, Provinsi Jambi: Identification of Reptiles (Suborder Serpentes) in the Peat Ecosystem of Pematang Rahim Village Forest, East Tanjung Jabung Timur, Jambi Province - Wulan, Cory; Zori, M. Afwan; Khabibi, Jauhar (Jurnal Silva Tropika, 2026)
ABSTRACT Snakes play a role in balancing the ecosystem, namely as pest controllers and being prey for other animal species that have a higher trophic level. Snakes can be found from lowlands to highlands, both in the soil, trees, freshwater, brackish water to seawater except in areas with low temperatures such as the poles. One of the natural habitats of snake distribution in Jambi Province is in the peat ecosystem in the Pematang Rahim Village Forest, East Tanjung Jabung Regency. The purpose of this study was to identify and analyze the level of diversity of snake species of the suborder Serpentes found in the Pematang Rahim Village Forest, East Tanjung Jabung Regency, Jambi Province. The research method used in this study was Visual Encounter Survey combined with the Capture-Mark-Recapture (CMR) method for species identification. In the HDPR peat ecosystem, 33 individuals of the suborder Serpentes snakes from 16 species and 7 families were successfully identified, with the largest number of species coming from the Colubridae family, and the largest individual being the Tropidolaemus wagleri species. The Shannon-Wiener diversity value (H’) is 2.74 (moderate diversity), Margalef species richness (Dmg) is 4.29 (moderate species richness), and Evenness evenness (E) is 0.89 (high). The Sorensen community similarity index value for arboreal-aquatic habitats is 47.09%; aquatic-terrestrial habitats are 57.14% and arboreal-terrestrial habitats are 72.73%.   Keywords: peat ecosystem, Pematang Rahim Village Forest, species diversity, reptile, snakes   ABSTRAK Ular berperan sebagai penyeimbang ekosistem yaitu sebagai pengendali hama dan menjadi mangsa dari spesies satwa lain yang memiliki trophic level yang lebih tinggi. Ular bisa ditemukan dari dataran rendah hingga dataran tinggi, baik di dalam tanah, pohon, air tawar, air payau sampai perairan air laut kecuali daerah dengan suhu rendah seperti kutub. Salah satu habitat alami persebaran ular yang ada di Provinsi Jambi yaitu pada ekosistem gambut di Hutan Desa Pematang Rahim Kabupaten Tanjung Jabung Timur. Tujuan dari penelitian ini adalah untuk mengidentifikasi dan menganalisis tingkat keanekaragaman jenis ular sub ordo Serpentes yang terdapat di Hutan Desa Pematang Rahim Kabupaten Tanjung Jabung Timur Provinsi Jambi. Metode  penelitian  yang digunakan  dalam  penelitian  ini  adalah  Visual Encounter Survey yang dikombinasikan dengan metode Capture-Mark-Recapture  (CMR)  untuk  identifikasi  spesies. Pada ekosistem gambut HDPR berhasil teridentifikasi sebanyak 33 individu ular sub ordo serpentes dari 16 spesies dan 7 famili, dengan jumlah spesies terbanyak berasal dari famili Colubridae, dan inidvidu terbanyak yaitu spesies Tropidolaemus wagleri. Nilai keanekaragaman Shannon-Wiener (H’) yaitu sebesar 2,74 (keanekaragaman sedang), kekayaan spesies Margalef (Dmg) sebesar 4,29 (kekayaan spesies sedang), kemerataan Eveness (E) sebesar 0,89 (tinggi). Untuk nilai indeks kesamaan komunitas Sorensen untuk habitat arboreal-akuatik sebesar 47,09%; habitat akuatik-terestrial sebesar  57,14% serta habitat arboreal-terestrial sebesar 72,73%.   Kata kunci: ekosistem gambut, Hutan Desa Pematang Rahim, keanekaragaman spesies, reptil, ular